Walking to a number: is there affective involvement in generating the SNARC effect in numerical cognition? - Segal, Hanna; Tzelgov, Joseph; Algom, Daniel (Frontiers in Psychology, 2024)
The effect known as the spatial-numerical association of response codes (SNARC) documents fast reaction to small numbers with a response at the left and to large numbers with a response at the right. The common explanation appeals to a hypothetical mental number line of a left-to-right orientation with the numerical magnitudes on the line activated in an automatic fashion. To explore the possibility of emotional involvement in processing, we employed prototypical affective behaviors for responses in lieu of the usual spatial-numerical ones (i.e., of pressing lateralized keys). In the present series of experiments, the participants walked toward a number or walked away from a number (in a physical approach-avoidance setup) or said “good” or “bad” in response to a number. We recorded strong SNARC effects with affective responding. For example, it took participants longer to say “good” than “bad” to small numbers, but it took them longer to say “bad” than “good” to larger numbers. Although each particular outcome can still be accounted for by a spatial interpretation, the cumulative results are suggestive of the possibly of affective involvement in generating the effect.